Selection against instability: stable subgraphs are most frequent in empirical food webs. Issue 12 (6th March 2015) - Borrelli, Jonathan J.
Abstract : Food web structure can be characterized by the particular frequencies of subgraphs found within them. Although there are thirteen possible configurations of three species subgraphs, some are consistently over‐represented in empirical food webs. This is a robust pattern that is found across marine, freshwater or terrestrial environments. The preferential elimination of unstable subgraphs during the assembly of the food web can explain the observed pattern. It follows from this hypothesis that there should be differences in the stability of different subgraphs, and that stability should be positively correlated to their frequency in food webs. Using 50 food webs collected from a variety of databases I determined the frequency of each of the thirteen possible subgraphs with respect to randomized webs. Then by numerical simulation I determined the quasi sign stability (QSS) of each subgraph. My results clearly show a positive correlation between QSS and over‐representation of the different subgraphs in empirical food webs.